Dose‐dependent inactivation of airway tryptase with a novel dissociating anti‐tryptase antibody (MTPS9579A) in healthy participants: A randomized trial - Sharon M. Rymut; Siddharth Sukumaran; Gizette Sperinde; Meire Bremer; Joshua Galanter; Kenta Yoshida; Jordan Smith; Prajna Banerjee; Viyia Sverkos; Fang Cai; Verena Steffen; Lindsay M. Henderson; et al. (Wiley, 2022)
Abstract Tryptase is the most abundant secretory granule protein in human lung mast cells and plays an important role in asthma pathogenesis. MTPS9579A is a novel monoclonal antibody that selectively inhibits tryptase activity by dissociating active tetramers into inactive monomers. The safety, tolerability, pharmacokinetics (PKs), and systemic and airway pharmacodynamics (PDs) of MTPS9579A were assessed in healthy participants. In this phase I single‐center, randomized, observer‐blinded, and placebo‐controlled study, single and multiple ascending doses of MTPS9579A were administered subcutaneously (s.c.) or intravenously (i.v.) in healthy participants. In addition to monitoring safety and tolerability, the concentrations of MTPS9579A, total tryptase, and active tryptase were quantified. This study included 106 healthy participants (82 on active treatment). Overall, MTPS9579A was well‐tolerated with no serious or severe adverse events. Serum MTPS9579A showed a dose‐proportional increase in maximum serum concentration (Cmax) values at high doses, and a nonlinear increase in area under the curve (AUC) values at low concentrations consistent with target‐mediated clearance were observed. Rapid and dose‐dependent reduction in nasosorption active tryptase was observed postdose, confirming activity and the PK/PD relationship of MTPS9579A in the airway. A novel biomarker assay was used to demonstrate for the first time that an investigative antibody therapeutic (MTPS9579A) can inhibit tryptase activity in the upper airway. A favorable safety and tolerability profile supports further assessment of MTPS9579A in asthma. Understanding the exposure‐response relationships using the novel PD biomarker will help inform clinical development, such as dose selection or defining patient subgroups.